Implementasi Pembelajaran MatematikaDengan Model Pembelajaran Pbl Berbasis Nht Dan GiDitinjau Dari Komunikasi Matematis - Maradani, Anta Vini, Dra. Nining Setyaningsih, M.Si (2016)
The aims of this research are to analysis: (1) the effect of PBL (Problem Based Learning) model based NHT (Number Heads Togeteher) and PBL (Problem Based Learning) model based GI (Group Investigation) in mathematics learning outcomes (2) the effect of mathematic communication in mathematics learning outcomes (3) the interaction between PBL (Problem Based Learning) model based NHT (Number Heads Togeteher) and GI (Group Investigation) with mathematical communicatin in mathematics learning outcomes. This research is a experimental research to treat learning model. The sample of this research is determined by cluster random sampling technique, in order to obtain VIII B as the experimental class and VIII A as the control class. The instrument of this research used a creative of ability questionnaire and mathematics achievement test. The collected data were analyzed using two way ANOVA and then Sceffe test. The results showed that: (1) there is effect of PBL (Problem Based Learning) model based NHT (Number Heads Togeteher) and PBL (Problem Based Learning) model based GI (Group Investigation) in mathematics learning outcomes, with FA = 5,56, (2) there is effect of mathematic communication in mathematics learning outcomes, with FB = 19,61, (3) there is no interaction between PBL (Problem Based Learning) model based NHT (Number Heads Togeteher) and GI (Group Investigation) with mathematical communicatin in mathematics learning outcomes, with FAB = 0,113.